Intensi Kewirausahaan Dikalangan Mahasiswa Ditinjau dari Motivasi Berprestasi dan Ketakutan pada Kegagalan - Farradinna, Syarifah; Fikri, Fikri (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
Educated unemployment in Indonesia has been alarming. To overcome the need to review psychologically besides physical steps taken. This study aims to describe and test psychological characteristics (achievement motivation and fear of failure) that affect university students' entrepreneurial intentions. This object research is 233 students at one of Pekanbaru universities, who were selected using a stratified random sampling technique. The analysis used in this study is confirmatory factor analysis from MPlus from Harrington (2009) and Chi-Square analysis to test the significance of the estimated variables. The measuring instrument consists of 3 scales, namely the scale of entrepreneurial intentions, the scale of achievement motivation, and the scale of fear of failure. The analysis results show that there is an influence of achievement motivation and fear of failure on entrepreneurial intentions among university students. This research implies that academics always hold seminars and training related to psychoeducation in overcoming negative affective problems to reduce the fear of failure among students to become entrepreneurs.